Seismic risk of Open Spaces in Historic Built Environments: A matrix-based approach for emergency management and disaster response. (November 2021) - Bernabei, L.; Mochi, G.; Bernardini, G.; Quagliarini, E.
Abstract: Earthquakes affect the safety of the users hosted in both indoor and outdoor urban built environments, especially in Historic Built Environments (HBEs). Many full HBE-scale risk-assessment methods are defined, while methodologies oriented to local analysis of meso-scale elements, such as Open Spaces (OSs), are still limited. Nevertheless, OSs play a crucial role in the first emergency phases, like in the evacuation process, since they host emergency paths and gathering areas. The seismic risk of an OS mainly depends on the combination of the damage suffered from facing buildings and the exposure, which mainly refers to the quantification of human lives. Damage levels result from the combination of vulnerability and hazard-related issues, while exposure is essentially affected by the number of OS users, whose spatial distribution is strongly time-dependent. Methods to quickly combine these issues are needed, especially in view of the deeper insights for the implementation of risk-reduction strategies (i.e. according to simulation-based approaches). This work offers a novel methodology to quickly perform Seismic Risk Assessment and Management of an OS by correlating damage levels to exposure-related issues. The method is composed of two specific matrices, which are developed according to quick literature-based approaches prone to rapid meso-scale applications in HBEs, also by non-expert technicians. The "damage matrix" links the site hazard to the building vulnerability. The assessed damage levels are combined with the users' exposure into the "consequences matrix", to estimate the risk in emergency conditions for the OS users, thus supporting decision-makers in promoting robustness/preparedness strategies. Highlights: Earthquake risk of Open Spaces in Historic Built Environments is investigated. Existing quick methods for hazard, vulnerability and exposure assessment are combined. The matrix considering the damage of building facing the Open Space is linked to its users' exposure. The damage-exposure correlation provides a "consequence matrix" to assess and manage risk of Open Spaces. The matrix results are organized to suggest robustness and preparedness strategies for the Open Spaces.